Making Room for Social Responsibility in Translator Training - İlmek, Seda Taş (English Studies at NBU, 2022)
This study examines how the integration of social responsibility into translator training contributes to the learning and development of translation students. To this end, an action research design and an innovative situated learning project were implemented in an existing Bachelor’s course in Translation and Interpreting. Students voluntarily performed two types of authentic translation tasks for a non-profit foundation and wrote project reports. The reports suggest that the integration of social responsibility into translator training raises the awareness of social responsibility among translation students and thus contributes to the improvement of their knowledge. It also has the potential to offer translation students a real experience and develop their translator competences. Therefore, this study proposes linking social responsibility with different learning environments in translator training because making room for social responsibility allows students to develop as socially responsible translators.